Antiseptic chlorhexidine in activated sludge: Biosorption, antimicrobial susceptibility, and alteration of community structure. (1st May 2019) - Keerthisinghe, Tharushi P.; Nguyen, Luong N.; Kwon, Eilhann E.; Oh, Seungdae
Abstract: Chlorhexidine (CHX) is a broad-spectrum antimicrobial, which may pose environmental health risks. This study examined the removal potential and the mechanisms regulating the fate of CHX in activated sludge (AS). Bioreactors inoculated with AS removed 74 ± 8% and 81 ± 6% of CHX at steady state while receiving 0.5 and 1 mg/L CHX, respectively. Analysis of the removal pathways showed that biosorption, rather than biological breakdown or other abiotic losses, largely (>70%) regulated the removal of CHX. 16S rRNA gene-based analysis revealed that CHX selected for Luteolibacter (4.3–10.1-fold change) and Runella (6.2–14.1-fold change) with potential multi-drug resistance mechanisms (e.g., efflux pumps). In contrast, it significantly reduced core members ( Comamonadaceae and Flavobacteriaceae ) of AS, playing a key role in contaminant removal and floc formation directly associated with the performance of WWTPs (e.g., wastewater effluent quality). Antimicrobial susceptibility testing showed that 0.4–1.3 mg/L of CHX can be sublethal to AS. Our work provided new insights into the fate of CHX in urban waste streams and the potential toxicity and effects on the structure and function of AS, which has practical implications for the management of biological WWTPs treating CHX. Graphical abstract: Image 1 Highlights: Activated sludge-inoculated bioreactors removed 70–80% of CHX at steady state. CHX was removed in activated sludge largely by biosorption. CHX could be inhibitory to activated sludge at environmentally relevant levels. CHX selected for Luteolibacter and Runella with potential multi-drug resistance mechanisms. CHX reduced core members of activated sludge .